Relationships between parental and peer attachment, social support, coping strategies and stress among Iranian adolescents living in Malaysia - Rabbani, Mohtaram (2015)
Understanding the factors contributing to stress among adolescents is vital for effective intervention. Parental attachment and peer attachment, as speculated in attachment theory by Bowlby (1982), are key factors of stress among adolescents. According to Transactional Model of Stress Lazarus (1987), social support is coping resources that has effect on stress. The effect of parental attachment, peer attachment, social support on stress could be influenced by coping strategies, as an internal factor. The present study was designed to examine the influence of parental attachment, peer attachment and social support on stress among adolescents, and to examine the mediating role of coping strategies on these relationships. This study utilized correlational study design using survey method. A total of 150 students aged between 12 and 18 years old was selected as respondents for this study using simple random sampling method. This study was conducted at one private and two public Iranian schools in Kuala Lumpur, Malaysia. Findings from this study illustrated that there are significant and negative relationships between parental attachment, peer attachment and stress among Iranian adolescents living in Malaysia. Adolescents with secure attachment to parents have less stress. In addition, the relationship between social support and stress was negative and significant. So, adolescents with higher social support from important persons in their lives have lower stress. Furthermore, the results of mediation analysis suggest that coping strategies mediated the relationships between parental attachment, peer attachment, social support and stress. Emotion-focused coping strategy has the mediation effect on the relationship between parental attachment and stress. Both problem-focused and emotion-focused coping strategy has the mediation effect on the relationships between peer attachment and stress. Emotion-focused coping strategy has a mediation effect on the relationship between social support and stress. Social support is the strongest predictor of stress in this study. Other significant predictors of stress are parental attachment, peer attachment, problemfocused coping strategy and emotion-focused coping strategy. Parental attachment, peer attachment and social support are related to stress and the mediation findings suggests that coping strategies play complementary role on the relationship between parental attachment and peer attachment, social support, and stress. The study advances understanding on the important influences of parental attachment, peer attachment, social support and coping strategies on stress among adolescents. This investigation provides insights into the individual and environmental factors that are related to stress that can be beneficial to parents,school psychologist, counsellors and teachers.